Odpowiedzi

  • Użytkownik Zadane
2009-09-22T17:57:15+02:00
Po 1 roku - 10600
Po 2 latach - 10600*1.06 = 11236
Po 3 latach - 11236*1.06=11910.16
2009-09-22T17:59:59+02:00
10000 zł * 0,06 = 600zł
po pierwszym roku
10600
10600 * 0,06 = 636
drugim
11236
11236 * 0,03= 674,16

1236 + 674,16 = 1910,16

Odp. zysk wyniesie 1910,16 zł
Najlepsza Odpowiedź!
2009-09-22T18:02:19+02:00
1 rok :
10000*6%= 10000*6/100= 600
10000+600=10600(zł)

2 rok:
10600*6%=10600*6/100=636
10600+636=11236(zł)

3 rok:
11236*6%=11236*6/100=674,16
11236+674,16=11910,16 (zł)

Zysk:
11910,16-10000=1910,16

Nie wiem czy o to Ci chodzi...

10000 - 100%
x - 6%

x=10000*6%/100 itd.